Discovering God’s Will: Paley’s Problem with Special Reference to ‘The Christian Sabbath’ - Cole, Graham A. (Tyndale bulletin, 1988)
An exploration of William Paley’s role as a Christian ethicist, noting how his theological utilitarianism raises certain fundamental questions, of continuing importance, about the relationship between religion and ethics.